Effect of Oxygen Contamination on Propionate and Caproate Formation in Anaerobic Fermentation - Baleeiro, Flávio C. F.; Ardila, Magda S.; Kleinsteuber, Sabine; Sträuber, Heike (Frontiers in Bioengineering and Biotechnology, 2021)
Mixed microbial cultures have become a preferred choice of biocatalyst for chain elongation systems due to their ability to convert complex substrates into medium-chain carboxylates. However, the complexity of the effects of process parameters on the microbial metabolic networks is a drawback that makes the task of optimizing product selectivity challenging. Here, we studied the effects of small air contaminations on the microbial community dynamics and the product formation in anaerobic bioreactors fed with lactate, acetate and H2/CO2. Two stirred tank reactors and two bubble column reactors were operated with H2/CO2 gas recirculation for 139 days and 116 days, respectively, at pH 6.0 and 32℃ with a hydraulic retention time of 14 days. One reactor of each type had periods with air contamination (between 97 ± 28 and 474 ± 33 mL O2 L-1 d-1, lasting from 4 to 32 days), while the control reactors were kept anoxic. During air contamination, production of caproate and CH4 was strongly inhibited, whereas no clear effect on n-butyrate production was observed. In a period with detectable O2 concentrations that went up to 18%, facultative anaerobes of the genus Rummeliibacillus became predominant and only n-butyrate was produced. However, at low air contamination rates and with O2 below the detection level, Coriobacteriia and Actinobacteria gained a competitive advantage over Clostridia and Methanobacteria, and propionate production rates increased to 0.8 – 1.8 mmol L-1 d-1 depending on the reactor (control reactors 0.1 – 0.8 mmol L-1 d-1). Moreover, i-butyrate production was observed, but only when Methanobacteria abundances were low and, consequently, H2 availability was high. After air contamination stopped completely, production of caproate and CH4 recovered, with caproate production rates of 1.4 – 1.8 mmol L-1 d-1 (control 0.7 – 2.1 mmol L-1 d-1). The results underline the importance of keeping strictly anaerobic conditions in fermenters when consistent caproate production is the goal. Beyond that, micro-aeration should be further tested as a controllable process parameter to shape the reactor microbiome. When odd-chain carboxylates are desired, further studies can develop strategies for their targeted production by applying micro-aerobic conditions.